A review on the potential of filamentous fungi for microbial self-healing of concrete - Aurélie Van Wylick (BMC, 2021)
Abstract Concrete is the most used construction material worldwide due to its abundant availability and inherent ease of manufacturing and application. However, the material bears several drawbacks such as the high susceptibility for crack formation, leading to reinforcement corrosion and structural degradation. Extensive research has therefore been performed on the use of microorganisms for biologically mediated self-healing of concrete by means of CaCO3 precipitation. Recently, filamentous fungi have been recognized as high-potential microorganisms for this application as their hyphae grow in an interwoven three-dimensional network which serves as nucleation site for CaCO3 precipitation to heal the crack. This potential is corroborated by the current state of the art on fungi-mediated self-healing concrete, which is not yet extensive but valuable to direct further research. In this review, we aim to broaden the perspectives on the use of fungi for concrete self-healing applications by first summarizing the major progress made in the field of microbial self-healing of concrete and then discussing pioneering work that has been done with fungi. Starting from insights and hypotheses on the types and principles of biomineralization that occur during microbial self-healing, novel potentially promising candidate species are proposed based on their abilities to promote CaCO3 formation or to survive in extreme conditions that are relevant for concrete. Additionally, an overview will be provided on the challenges, knowledge gaps and future perspectives in the field of fungi-mediated self-healing concrete.